Injury Profile in Elite Female Basketball Athletes at the Women's National Basketball Association Combine. (March 2013) - McCarthy, Moira M.; Voos, James E.; Nguyen, Joseph T.; Callahan, Lisa; Hannafin, Jo A.
Background: Anterior cruciate ligament (ACL) and meniscus injuries are common in female athletes participating in cutting and pivoting sports such as basketball. The epidemiological characteristics of injury in athletes seen at the Women's National Basketball Association (WNBA) combine and the effect of ACL reconstruction and meniscus surgery on longevity in the WNBA are unknown. Purpose: To evaluate the details and spectrum of injuries in athletes entering the WNBA combine and to assess the potential effect of specific injuries on the round drafted into the WNBA and career length. Study Design: Descriptive epidemiology study. Methods: Demographic data and the documented collegiate injury profile were reviewed from the WNBA database for all players entering the WNBA combine in 2000-2008. The study included injury data on 506 athletes. Complete demographic data were available for 496 players. Results: Of the athletes taking part in the combine, 45.2% were guards, 33.7% were forwards, and 21.1% were centers. Ankle sprain (47.8% of players), hand injury (20.8%), patellar tendinitis (17.0%), ACL injury (15.0%), meniscus injury (10.5%), stress fracture (7.3%), and concussion (7.1%) were the most common injuries reported. Seventy-three athletes (14.4%) reported ACL reconstruction before entering the WNBA combine, and meniscus surgery was the next most common surgery (n = 50 players; 9.9%). There were no differences in ACL or meniscus surgery when analyzed by player position or round drafted. History of ACL or meniscus surgery did not affect career length in the WNBA. Excluding ACL and meniscus surgery, other reported surgical procedures were knee arthroscopic surgery (11.7%), ankle reconstruction (2.6%), and shoulder stabilization (2.0%). Conclusion: The ankle is the most common site of injury and ACL reconstruction is the most common surgery in elite female athletes participating in the WNBA combine. A history of injury or surgery did not affect the round drafted or career length.